Percutaneous & Mini Invasive Achilles tendon repair - Carmont Michael R; Rossi Roberto; Scheffler Sven; Mei-Dan Omer; Beaufils Philippe (BMC, 2011)
Abstract Rupture of the Achilles tendon is a considerable cause of morbidity with reduced function following injury. Recent studies have shown little difference in outcome between the techniques of open and non-operative treatment using an early active rehabilitation programme. Meta-analyses have shown that non-operative management has increased risk of re-rupture whereas surgical intervention has risks of complications related to the wound and iatrogenic nerve injury. Minimally invasive surgery has been adopted as a way of reducing infections rates and wound breakdown however avoiding iatrogenic nerve injury must be considered. We discuss the techniques and outcomes of percutaneous and minimally invasive repairs of the Achilles tendon.